Health risk assessment of potentially hazardous elements in mining wastes from barite deposit (Boucaïd, western Algeria) - Senouci, Khouloud; Bounouala, Mohamed; Boumaza, Bilal; Sasmaz, Ahmet; Yahyaoui, Sami; Ramesh, RamyaPriya; Kechiched, Rabah (Elsevier, 2025)
Barite-Lead-Zinc tailings pose environmental risks due to Potentially Hazardous Elements (PHEs). This study monitored PHE concentrations in the Bouca & iuml;d Ba-(Pb-Zn) mine, Algeria, and assessed related health risks. Various samples (raw rock, commercial products, and waste materials) were analyzed using SEM-EDX, XRD, FTIR, XRF, and ICP-MS, with multivariate statistics and Monte Carlo simulations for elemental correlation and risk assessment. Results showed a shared mineralogical composition of sphalerite, barite, dolomite, quartz, and calcite. BaO levels ranged from 4.33 to 45.15 wt% in all samples, with higher concentrations in finer particles, sludge, and dust (average 21.43, 37.82, and 39.51 wt%, respectively). Cyclone (dust) and classifier (sludge) waste had lower PHE concentrations, but finer fractions (f<(0.045 mm) to f(0.125-0.25mm)) exhibited elevated Cr, Fe, Ni, Zn, As, Cd, Sb, Hg, Tl, and Pb. Cadmium, As, Pb, and Zn exceeded WHO and Canadian limits. Health risk assessments showed Hazard Index (HI) values > 1 for non-carcinogenic and carcinogenic elements, particularly Sb, Zn, Cd, Fe, As, and Pb in children and As and Pb in adults. Lifetime cancer risk (LCR) values for As, Cd, Ni, and Pb exceeded US EPA thresholds, with children facing the highest risks. Probabilistic simulations confirmed significant carcinogenic risks, underscoring the need for urgent mitigation.
Keywords: Ba-Pb-Zn ore; Mine waste; Grain size fractions; Potentially hazardous elements (PHEs); Health risk assessment; Monte Carlo simulation